Gender Difference in the Association Between Stroke Knowledge and Health Behavior Before the Onset of Stroke Among Chinese Hypertensive Patients. Issue 4 (10th August 2021) - Li, Zhuo-Ran; Ruan, Heng-Fang; Shen, Li-Ping; Zhang, Xiao-Pei; Wan, Li-Hong
Abstract : Supplemental digital content is available in the text. ABSTRACT: BACKGROUND: Previous research has shown that men and women have different levels of stroke knowledge and differing health behaviors, which are important factors affecting blood pressure, as hypertension is a key risk factor for stroke occurrence. There has been little research on the effects of sex on the association between these 2 variables before the onset of stroke among Chinese hypertensive patients. METHODS: A cross-sectional study and a convenience sampling method were used. 272 male and 118 female hypertensive stroke patients were recruited. Each patient completed the Stroke Knowledge Questionnaire and the Health Behavior Scale for stroke patients. RESULTS: Compared with female patients, male patients had greater stroke knowledge and worse prestroke health behavior. The Pearson correlation coefficient between stroke knowledge and prestroke health behavior was 0.149 and 0.223 in male and female participants, respectively, P < .05. The results of a multiple regression analysis showed that Chinese hypertensive stroke patients' prestroke health behavior was significantly influenced by sex and stroke knowledge. CONCLUSION: Chinese male and female hypertensive stroke patients had disparities in stroke knowledge and prestroke health behavior; moreover, the correlation between these 2 variables before experiencing a hypertensive stroke was different between men and women. Men with hypertension should be considered at a higher risk for an initial or recurrent stroke. Developing sex-specific intervention for primary or secondary stroke prevention in China is essential.